Edukasi pencegahan mual muntah pada pasien p reoperatif Sectio Caesarea - Jonatan Aris Maraya; Rahmaya Nova Handayani; Magenda Bisma Yudha (THE JOURNAL OF Nursing Management Issues, 2025)
Background: Postoperative nausea and vomiting (PONV) in Sectio Caesarea patients is a significant clinical problem that is often overlooked. The high incidence of PONV in Sectio Caesarea patients, based on the pre-survey, reached 42.8%–45.6%. PONV is the most common side effect after postoperative pain, depending on patient risk factors and the preventive strategies implemented. This condition may lead to serious complications such as wound dehiscence, aspiration, dehydration, prolonged hospitalization, and increased healthcare costs. Purpose: To measure changes in knowledge after education on nausea and vomiting prevention among preoperative Sectio Caesarea patients. Method: This community service activity used a participatory and educational approach with a preoperative educational intervention design. The study was conducted at the Central Surgical Installation of RSUD Merauke from May to June 2026, involving 30 preoperative Sectio Caesarea patients. Results: The majority of respondents were aged 20–35 years (76.7%) and multigravida (76.7%). The pre-test results showed that 70.0% of respondents were in the moderate category and 30.0% in the poor category. After the educational intervention, 83.3% were in the good category and 16.7% in the moderate category, with no respondents remaining in the poor category. Conclusion: Structured, communicative, and easy-to-understand preoperative education effectively improved patients’ understanding of nausea and vomiting prevention, supported patient preparedness for Sectio Caesarea, and has the potential to become an educational intervention model in preoperative services at RSUD Merauke.   Keywords: Cesarean Section; Education; Nausea and Vomiting.   Pendahuluan: Post operative nausea vomiting (PONV) pada pasien Sectio Caesarea merupakan masalah klinis yang signifikan dan sering kali diabaikan. Tingginya kejadian PONV pada pasien Sectio Caesarea, yang berdasarkan pra-survei mencapai 42.8%–45.6%. PONV menjadi efek samping yang paling umum setelah nyeri pascaoperasi, tergantung faktor risiko pasien serta strategi pencegahan yang diterapkan. Keadaan ini berpotensi menyebabkan komplikasi serius seperti dehiscence luka operasi, aspirasi, gangguan hidrasi, serta memperpanjang masa rawat dan biaya perawatan. Tujuan: Untuk mengukur perubahan pengetahuan setelah edukasi pencegahan mual muntah pada pasien p reoperatif sectio caesarea. Metode:  Kegiatan Pengabdian Masyarakat dengan pendekatan partisipatif dan edukatif dan desain intervensi edukasi preoperatif. Dilaksanakan di Instalasi Bedah Sentral Rumah Sakit Umum Daerah (RSUD) Merauke pada Mei–Juni 2026 dengan melibatkan 30 pasien preoperatif Sectio Caesarea. Hasil: Mayoritas responden berusia 20–35 tahun (76.7%) dan multigravida (76.7%). Pre-test menunjukkan 70.0% responden dalam kategori cukup dan 30.0% kurang. Setelah edukasi, 83.3% berada pada kategori baik dan 16.7% cukup, tanpa responden kategori kurang. Simpulan: Edukasi preoperatif yang terstruktur, komunikatif, dan mudah dipahami efektif meningkatkan pemahaman pasien mengenai pencegahan mual muntah, mendukung kesiapan pasien menghadapi sectio caesarea, dan berpotensi menjadi model intervensi edukatif dalam pelayanan preoperatif di RSUD Merauke.   Kata Kunci: Edukasi, Mual Muntah, Sectio Caesarea.